Poverty and corporate social responsibility in Africa: a critical assessment - Matunhu, Jephias (ZOU Publications, 2016)
The desktop study is on poverty and underdevelopment, which continues to be a matter of concern in the developing world. According to Chen and Ravallion (2008), about 1.4 billion people (one in four) lived on less than $1.25 a day in 2005. The above situation is likely to worsen in Africa where governments are failing to eradicate poverty alone. Giant transnational corporations (TNC) are increasingly called upon to champion poverty reduction in the continent. Notably, of the world’s 100 largest economic entities, 51 are giant TNCs and the world’s 200 largest corporations have combined sales that are greater than the combined GDP of all countries in the world. This desktop research assumes that bodies corporate are the key institutions for eradicating poverty in Africa; and so are called upon to make a significant contribution to the society that they operate in and depend upon for their economic and financial might. More specifically, this paper examines the role of giant TNCs in poverty reduction in a continent that has high poverty levels but endowed with plentiful resources.